Analisis Fatwa DSN MUI Tentang Murabahah dan Wakalah Bil Ujroh dalam Fintech Dana Syariah - Iqlima Fahrunisa; Basmah Nafisah (LABATILA : Jurnal Ilmu Ekonomi Islam, 2023)
Dana Syariah is an Islamic Financial Institution platform that adheres to Islamic economic principles. Dana Syariah issues financing product schemes based on Sharia Crowdfunding and Sharia peer to peer lending, so that the contracts commonly used in Sharia Fund transactions are murabhahah and wakalah bil ujroh. This article attempts to develop an argument by conducting an exploratory empirical study with a qualitative approach. Data sources were obtained through interviews and looking for references related to the research theme. In analyzing the actual practice of Sharia Funds, the author also explores the DSN MUI fatwa and the yellow book literature which explains the contracts used. This research found that there is a discrepancy between the practices carried out in Islamic Funds and the principles of Islamic economics contained in the fatwa of the Sharia National Council of the Indonesian Ulema Council.